NGHIÊN CỨU CHU TRÌNH CHUYỂN HÓA AMONI TRONG HỆ THỐNG TUẦN HOÀN NƯỚC ƯƠNG NUÔI CÁ BIỂN BẰNG BỂ LỌC SINH HỌC NGẬP NƯỚC - Thu Hiền, Nguyễn Thị; Nhân, Trần Văn; Cự, Nguyễn Đức; Thanh Hương, Nguyễn Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY AMMONIA REMOVE IN THE SUBMERGED BIOFILTER APPLIED FOR RECIRCULATION SYSTEM AQUACULTURE WATER MARINE FISH REARING Ammonia removal by a submerged biofilter with the growth and detachment of biofilm on the media. Maintaining an active biofilm in a biofilter is a necessary requirement. The experiment carried out to determine activation time, to investigate the effects of operating parameters such as: temperature, TAN (Total Ammonia Nitrogen), Volume TAN Rate (VTR) and specific ammonia removal rate (SNR). The results showed that the start of the operation into stable operation is 21 – 22 days. The experimental results were used to develop a series of equations describing the relationship between ammonia removals and operating conditions (SNR, temperature, concentrations of ammonia). Operating system stable and water quality requirements are demonstrated by graphs. These correlation equations SNR with temperature and TAN in recirculation aquaculture system were set up. The observed values were within the 90% confidence interval of the model. Thus, the model Biofilter to select a backwash frequency that will maintain a stable water quality in recirculating aquaculture systems and toward application for industrial marine fish production. Keywords. TAN, Biofilter, Recirculating aquaculture systems (RAS).